2006
DOI: 10.1143/jjap.45.5535
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structure Analysis of Very Long ErSi2 Nanowires Formed on Si(110) Substrates

Abstract: Very long ErSi2 nanowires were formed on a Si(110) substrate by a self-assembly process. The wires were highly parallel and grew in the Si<011> direction. Nanowires with lengths more than 50 µm were fabricated. It was observed by transmission electron microscopy that the wires were hexagonal crystal type, having their c-axis (<0001> direction) perpendicular to the Si(112) plane. Then the nanowires were deeply buried in the Si(110) surface. Energy-dispersive X-ray spectroscopy measurements indicated that the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The electrical resistance of the ErSi 2 nanowire has been measured at room temperature by depositing two Au electrodes on the ends of the nanowire, and the electrical resistivity is approximately 9 × 10 -4 Ωcm [5]. This result suggests that the ErSi 2 nanowire can be used as a nano connective material.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The electrical resistance of the ErSi 2 nanowire has been measured at room temperature by depositing two Au electrodes on the ends of the nanowire, and the electrical resistivity is approximately 9 × 10 -4 Ωcm [5]. This result suggests that the ErSi 2 nanowire can be used as a nano connective material.…”
Section: Introductionmentioning
confidence: 90%
“…The crystal structure of erbium silicide (ErSi 2 ) has the form of A 1 B 2 , belonging to the hexagonal system. It was reported [2][3][4][5]7] that the lattice mismatch between the c-axis of ErSi 2 and the Si (100) and (110) planes was larger than that between the a-axis and Si (100) and (110) planes, and so ErSi 2 nanowires could grow by a self-assembly process in a particular direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] In our previous work, we fabricated very long ErSi 2 nanowires on a Si(110) surface without the UHV system. [10][11][12] From the results of the structure analysis, it was found that the ErSi 2 nanowires were deeply buried in the Si(110) substrate, ErSi 2 was epitaxially grown, and its [0001] direction (c-axis) was oriented perpendicular to the Si( 111 1) plane. 11,12) In this study, we fabricated ErSi 2 nanowires on Si(100) substrate by the self-assembly growth process achieved by simple spin-coating and postannealing processes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] From the results of the structure analysis, it was found that the ErSi 2 nanowires were deeply buried in the Si(110) substrate, ErSi 2 was epitaxially grown, and its [0001] direction (c-axis) was oriented perpendicular to the Si( 111 1) plane. 11,12) In this study, we fabricated ErSi 2 nanowires on Si(100) substrate by the self-assembly growth process achieved by simple spin-coating and postannealing processes. With the use of a transmission electron microscope (TEM), surface and cross-sectional investigations were carried out to clarify the chemical composition and crystal structure of the wires.…”
Section: Introductionmentioning
confidence: 99%